Depositional environment and passive-to-active margin transition as recorded by trace elements chemistry of lowermiddle Palaeozoic detrital units from the Ossa-Morena Zone (SW Iberia) - Roseiro, José (2021)
New lithogeochemical data of Lower-Middle Palaeozoic metasedimentary rocks of the Ossa-Morena Zone are here presented and integrated with previously published data, as well as a discussion on their provenance and geotectonic settings. In the Cambrian – Lower Ordovician rift stages, metasediments mostly derived from an acid continental source with passive margin geochemical affinities, showing a significant recycled sediment component, as well as an oxidizing depositional environment. Metasediments related with the drift stage, during Ordovician and Silurian ages, display general geochemical features similar to those that characterize the Cambrian units, inferring the prevailing acid source and passive margin geotectonic settings, and slightly anoxic depositional conditions in the end of this stage. In turn, geochemistry of samples representative of the Devonian debris deposition contrast with the passive continental margin geochemical data; notwithstanding the dominant acid source, an increased trend for a basic/intermediate sedimentary component can be observed, thus inferring a contribution of an external volcanic (probably subductionrelated) source during Devonian ages. These interpretations are in accordance with other studies regarding north Gondwana rift and drift stages during Cambrian-Silurian times and active margin settings during Devonian.